2021
DOI: 10.1093/europace/euab250
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-function mutations in cardiac ryanodine receptor channel cause various types of arrhythmias including long QT syndrome

Abstract: Aims Gain-of-function mutations in RYR2, encoding the cardiac ryanodine receptor channel (RyR2), cause catecholaminergic polymorphic ventricular tachycardia (CPVT). Whereas, genotype–phenotype correlations of loss-of-function mutations remains unknown, due to a small number of analysed mutations. In this study, we aimed to investigate their genotype–phenotype correlations in patients with loss-of-function RYR2 mutations. Methods and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
1
24
2
Order By: Relevance
“…They suggested that patients with RYR2 variants and bradycardia should be carefully diagnosed to avoid misdiagnosing CPVT patients as LQTS patients [ 61 ]. Hirose et al revealed RYR2 loss-of-function mutations causing QT prolongation [ 62 ]. We found that most LQTS-related variants reported in previous studies [ 18 , 42 , 48 , 63 ] and in our present study were located on the large cytosolic region of the N-terminal side ( Fig 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that patients with RYR2 variants and bradycardia should be carefully diagnosed to avoid misdiagnosing CPVT patients as LQTS patients [ 61 ]. Hirose et al revealed RYR2 loss-of-function mutations causing QT prolongation [ 62 ]. We found that most LQTS-related variants reported in previous studies [ 18 , 42 , 48 , 63 ] and in our present study were located on the large cytosolic region of the N-terminal side ( Fig 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several publications support the fact that pathogenic variants in KCNQ1 , ANK2 , KCNE1 , KCNE2 , KCNH2 , KCNJ2 and SCN5A can lead to a complex overlapping phenotype of LQTS, CPVT and ventricular ectopy [ 42 , 48 , 92 ]. Hirose et al, recently described in a cohort of children (<16 years old) the association of loss-of-function pathogenic variants in RYR2 with various types of arrhythmia, including LQTS, VF and scTdP, depending on the alteration of channel activity [ 83 , 84 ]. The pathogenic variants p.I4855M and deletion of exon 3 in the RYR2 gene have been associated with the rare syndrome of left ventricular non-compaction (LVNC) overlap and CPVT, presenting a high lethality [ 85 ].…”
Section: Genetic Overlapmentioning
confidence: 99%
“…However, a recent study identified a loss-of-function mutation D3291V, which markedly reduced luminal Ca 2+ sensitivity, and blunted response to adrenergic stimulation, also exhibiting a CPVT phenotype ( 116 ). The relationship between gain-of-function or loss-of-function and the clinical phenotype still needs to be elucidated ( 117 ). The calsequestrin encoded by CASQ2 is a calcium-binding protein that regulates the amount of calcium released from the SR during excitation-contraction coupling by buffering the calcium in the SR ( 118 , 119 ).…”
Section: Genetic Factors Of Ventricular Arrhythmias Without Structura...mentioning
confidence: 99%